Day 2 Wed, October 21, 2015 2015
DOI: 10.2118/175904-ms
|View full text |Cite
|
Sign up to set email alerts
|

Carboxymethylcellulose a Cost Effective Alternative to Guar, CMHPG and Surfactant-Based Fluid Systems

Abstract: The first fracture treatment using crosslinked guar was performed in 1969. Since then guar and its derivative polymers have dominated hydraulic fracturing. But because of volatility and supply issues with guar gum that have surfaced during peak activity years, industry has turned to alternatives. One of those is Carboxymethylcellulose (CMC) that just like guar comes from food industry. CMC is also used in pharmaceuticals as a thickening agent, and in the oil and gas industry as an ingredient in drilling mud. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Hydroxypropyl methylcellulose (HPMC), another cellulose derivative, exhibits thermosensitive behavior due to partial methoxyl displacement by hydroxypropyl groups with gelation temperatures determined by the stability between hydrophilic and hydrophobic groups on its molecular chains. Azizov et al demonstrated that the incorporation of carboxymethyl cellulose within fracturing fluid systems can yield comparable production efficacy and reduced expenses compared to guar gum [51]. The industry is becoming more interested in employing polymers like carboxymethyl cellulose in hydraulic fractur- Later, the thermogelation phenomenon was observed in aqueous methylcellulose (MC) solutions where the solution forms a gel at high temperatures and reverts to a liquid state upon cooling [49].…”
Section: Employment Of Guar Gum and Its Derivatives In The Oil And Ga...mentioning
confidence: 99%
“…Hydroxypropyl methylcellulose (HPMC), another cellulose derivative, exhibits thermosensitive behavior due to partial methoxyl displacement by hydroxypropyl groups with gelation temperatures determined by the stability between hydrophilic and hydrophobic groups on its molecular chains. Azizov et al demonstrated that the incorporation of carboxymethyl cellulose within fracturing fluid systems can yield comparable production efficacy and reduced expenses compared to guar gum [51]. The industry is becoming more interested in employing polymers like carboxymethyl cellulose in hydraulic fractur- Later, the thermogelation phenomenon was observed in aqueous methylcellulose (MC) solutions where the solution forms a gel at high temperatures and reverts to a liquid state upon cooling [49].…”
Section: Employment Of Guar Gum and Its Derivatives In The Oil And Ga...mentioning
confidence: 99%
“…In the oil and gas industry, CMC is used as a gelling or thickening agent (also known as a viscosifier) that is added to water-based fracturing fluids to optimize proppant delivery into fractures created during hydraulic fracturing processes to keep the fissures open (Harris, 1988;Fink, 2013;Barbati et al, 2016). Over the years, different types of gelling agents, including guar gum and CMC, have been used by the energy industry depending on their availability and market pricing (Fink, 2013;Azizov et al, 2015). A recent study highlighted the sustainability of using CMC as the polymer of choice (compared to guar gum, for example) to deliver proppant to the fractures (Azizov et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, different types of gelling agents, including guar gum and CMC, have been used by the energy industry depending on their availability and market pricing (Fink, 2013;Azizov et al, 2015). A recent study highlighted the sustainability of using CMC as the polymer of choice (compared to guar gum, for example) to deliver proppant to the fractures (Azizov et al, 2015). CMC has also been proven to be an effective substitute to guar gum in fractured wells due to its better stability at high temperature (up to 90˚C), a better regain of conductivity after its degradation, and for superior proppant suspension (Aliu, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A typical water-based fracturing fluid contains a polymer thickening agent, clay stabilizer, crosslinker, buffer system, and a gel breaker. Different polymers have been used as thickeners, such as starches and cellulose derivatives [ 17 , 18 , 19 ]. However, the most common fracturing fluid polymers are guar gum and its two main derivatives hydroxypropyl guar (HPG) and carboxymethyl hydroxypropyl guar (CMHPG) due to their high performance, relatively low price, and wide availability [ 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%